Mean-field theory for confinement transitions and magnetization plateaux in spin ice - Powell, Stephen (IOP, 2017)
We study phase transitions in classical spin ice at nonzero magnetization, by introducing a mean-field theory designed to capture the interplay between confinement and topological constraints. The method is applied to a model of spin ice in an applied magnetic field along the [1 0 0] crystallographic direction and yields a phase diagram containing the Coulomb phase as well as a set of magnetization plateaux. We argue that the lobe structure of the phase diagram, strongly reminiscent of the Bose–Hubbard model, is generic to Coulomb spin liquids.